Analyses of growth performance and realized heritability of Pampus argenteus in a breeding program in China - Zhang, Cheng; Jacques, Kimran Jean; Zhang, Shun; Xu, Shanliang; Wang, Yajun; Wang, Danli (Frontiers in Marine Science, 2022)
Silver pomfret (Pampus argenteus) is an economically important mariculture species. However, little is known about the genetic parameters of its commercially important traits. In order to determine whether continuous progress can be achieved by selection for growth, we took the body weight trait of East China Sea P. argenteus as the target trait of mass selection. The realized heritability of P. argenteus from the selected group and control group were analyzed at the three growth times (60 d, 90 d and 120 d). The results showed that the growth performance parameters of the selected group in the third month post hatching were higher than those in the control group, but the opposite results were found in the fourth month. The morphological traits highly correlated with the body weight of P. argenteus were found by Pearson correlation analysis and path analysis, which were body length and tail length, respectively. On the 60th, 90th and 120th day after hatching, the genetic gains of body weight trait in the selected group were 9.44%, 17.64% and 15.18%, respectively, and the mean values of realized heritability were at moderate level. Nevertheless, in selected group, the genetic variation values of the two morphological traits significantly related to body weight were all below 10%, and the genetic gains were relatively low and stable, but the genetic variation values of body weight trait in the selected group were above 20%, and genetic gains were relatively high. These implied that it is possible to obtain considerable genetic gains by selecting for body weight trait, and the results provides supportive evidence for the continuity of the P. argenteus selective breeding program.